La agroecología con enfoque transversal profesional en el rediseño de la malla curricular de la carrera de tecnología en agropecuaria del instituto tecnológico agropecuario Manuel Isaac Encalada Zúñiga del sitio Pagua, cantón El Guabo, provincia de El Oro, en el periodo lectivo 2013 – 2014. - Asaaf Fernández, Lidia Pilar (2015)
The research related to "AGROECOLOGY WITH CROSS THE PROFESSIONAL APPROACH IN THE REDESIGN OF THE CURRICULUM MESH RACE IN AGRICULTURAL TECHNOLOGY INSTITUTE OF TECHNOLOGY SUPERIOR" MANUEL ISAAC ENCALADA ZÚÑIGA "Pagua SITE, THE CANTON GUABO, PROVINCE OF GOLD, for school year 2013 - 2014 ", requires teachers and the upper level of the career of agricultural technology, are updated regarding mainstreaming agro ecological according to the rules of the national plan of good living and food sovereignty.